The Influence Of Financial Distress, Return On Assets (ROA) And Company Size On Profit Management (Study On Pharmaceutical Companies Listed On The Indonesian Stock Exchange (BEI) In 2016-2022) - Nastiti Rizky Shiyammurti; Elis Citra Lestari (Sean Institute, 2024)
The aim of this research is to examine and analyze the influence of financial distress, Return on assets (ROA) and company size on earnings management in Food and Beverage Companies listed on the Indonesia Stock Exchange in 2016 -2022 . Financial distress uses model Altman Z - score , return on assets and company size ( size ) which are measured using natural logarithms. The total sample used in this research was 8 companies through purposive sampling. The data used in this research is secondary data. To test the hypothesis in this research, the multiple linear regression analysis method was used with a significance level of 0.05 using eviews 12 . The coefficient of determination in this research is 5 7 % which can be explained by the independent variables, namely financial distress, return on assets (ROA) and company size on earnings management variables . The results of this research indicate that financial distress influences earnings management , return in assets (ROA) influences earnings management , but company size has no influence on earnings management . Financial distress, return on assets and company size influence simultaneously or together on earnings management in pharmaceutical companies listed on the Indonesia Stock Exchange (BEI). Because the significance level is <0.05.